2007
DOI: 10.1002/rcm.3166
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of phenolic compounds in Erigeron breviscapus by liquid chromatography coupled to electrospray ionization mass spectrometry

Abstract: Erigeron breviscapus is an important herbal drug for the treatment of cardiovascular and cerebral vessel diseases. In this study, phenolic compounds were extracted from the whole plant of E. breviscapus and analyzed by high-performance liquid chromatography/electrospray ionization mass spectrometry. A total of 53 compounds were identified or tentatively characterized based on their UV and mass spectra. These compounds included caffeoylquinic acids (CQAs), CQA glucosides, malonyl-CQAs, acetyl-CQAs, caffeoyl-2,7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
47
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 25 publications
11
47
0
5
Order By: Relevance
“…These compounds presented a similar fragmentation pattern to the ones previously reported by Guimarães et al (2013). MS compounds with similar characteristics were also detected in E. breviscapus samples (Zhang et al, 2007Liao et al, 2010), which were respectively identified as erigoster B (3,9-diCDOA) and 4,9-diCDOA (or 3,4 diCDOA), so that those identities were tentatively assumed for the compounds observed in our case. The…”
Section: Compounds 1 ([M-h]supporting
confidence: 61%
See 1 more Smart Citation
“…These compounds presented a similar fragmentation pattern to the ones previously reported by Guimarães et al (2013). MS compounds with similar characteristics were also detected in E. breviscapus samples (Zhang et al, 2007Liao et al, 2010), which were respectively identified as erigoster B (3,9-diCDOA) and 4,9-diCDOA (or 3,4 diCDOA), so that those identities were tentatively assumed for the compounds observed in our case. The…”
Section: Compounds 1 ([M-h]supporting
confidence: 61%
“…-m/z at 705) could be associated to 3,4,9-triCDOA (Zhang et al, 2007 or to a diCDOA glucoside, as reported by Liao et al (2010). In our case, an identity as 3,4,9-triCDOA was assumed taking into account that for the diCDOA glucoside an elution earlier to the diCDOAs should be expected due to its greater polarity.…”
Section: Pseudomolecular Ion Of Compound 19 ([M-h]mentioning
confidence: 72%
“…Five groups of phenolic compounds such as phenolic acids, flavonol glycosides, flavan-3-ols, flavonoid aglycones and xanthones were recorded in HR cultures (Table 1). Their identification was based on the typical UV/Vis spectral data and LC/MS in the negative ionization mode [M-H] -with the subsequent MS 2 , MS 3 and MS 4 analysis for further identification with reference to similar data previously reported [24][25][26][27][28][29][30][31][32][33]. The HPLC analysis of secondary metabolites revealed marked differences between control roots ( Figure 3A) and HR cultures ( Figure 3B).…”
Section: Hplc/dad/esi-ms N Analysismentioning
confidence: 76%
“…HPLC chromatograms confirmed the presence of 5 phenolic acids (F1, F2, F4, F6 and F15) in root extracts (Table 1, Figure 3). Compound F1 with a molecular ion [M-H] -at m/z 191 was identified as quinic acid, taking in account its MS n fragmentation pattern [24]. Quinic acid (F1) was the only detectable phenolic acid in HR cultures.…”
Section: Hplc/dad/esi-ms N Analysismentioning
confidence: 99%
“…Compounds 20 (t R = 13.9 min), 21 (t R = 14.5 min), 23 (t R = 15.0 min), 26 (t R = 17.0 min) and 30 (t R = 19.6 min) displayed a [MÀH] À ion at m/z 601 and gave characteristic fragment ions of malonyl [MÀHÀ44] À at m/z 557 and [MÀHÀ86] À at m/z 515 (Zhang, Shi, Qu, & Cheng, 2007). However, their MS n fragment ions intensities were different and it was possible to characterise them by comparison with literature data.…”
Section: Malonylcaffeoylquinic Acidmentioning
confidence: 97%